The parental role before and after SIDS. Issue 10 (26th November 2022) - Plews-Ogan, Erin; Keywan, Christine; Morris, Sue E.; Goldstein, Richard D.
Abstract: Role confusion is a prominent constituent symptom of Prolonged Grief Disorder in parents after their infants die from sudden infant death syndrome (SIDS). We interviewed 31 parents of SIDS infants 2–5 years post-loss examining the parental role before death, at the time of loss, and in bereavement. Thematic analysis found disruption of the role and re-imagined responsibilities for their child's physical security, emotional security, and meaning. Tasks within these domains changed from concrete and apparent to representational and self-generated. Parents in bereavement locate ongoing, imperative parental responsibilities, particularly asserting their child's meaningful place in the world and in their family.